Police discretion, pragmatism and crime ‘deconstruction’: police doorstep crime investigations in England and Wales - Aplin, Rachael (Policing and society, 2022)
This article explores police discretionary practices associated with circumventing crime recording rules (NCRS), utilising doorstep crimes against elderly victims as the crime context (distraction burglary, fraud and attempts). This research examines 68 ‘rogue trader’ incidents from classified police systems, a focus group with CEnTSA trading standards officers and 31 police questionnaires from 26 England and Wales Force Intelligence Branches (FIB) and regional/national intelligence units. Almost half the doorstep incidents were filed at source with no investigation and 44% (30/68) of incidents breached National Crime Recording Standards (NCRS). It is argued that some officers deconstruct ‘crime’ utilising the power of language within their skilfully crafted summary ‘write up’. In justifying their dubious ‘no crime’ decisions, officers rely on identifiable ‘scripts’ that are reminiscent of the work of Shearing and Ericson (1991). A central script is that of ‘civil dispute’ which ‘legitimises’ the fraudster as entering into a contract with elderly victims ‘no matter how unscrupulous that contract may be’. Attendant officers deny property being stolen, suggest that elderly victims ‘consent’ to offender entry and even resort to the alleged unreliability or ‘confusion’ of elderly victims, despite this feature signifying a need for ‘enhanced’ safeguarding; all of which preclude officers from submitting crime reports. Findings expose ‘cuffing’ to be an enduring and dysfunctional police practice, effected out of self preference and pragmatism in order to ration workload. Such detrimental outcomes expose older people to repeat victimisation, under-policing and secondary victimisation by the state.